Corrosive esophagitis due to alkali ingestion in children: a case report - Felicia, Fabiola Vania; Sutarinda, Rina Desdwi Utami; Budiyanto, Budiyanto (Paediatrica Indonesiana, 2025)
Caustic ingestion is a relatively common event in childhood. History, identification of chemical substances, and clinical features are essential to predict the extension of damage and plan for diagnostic modalities and management. Thorough follow-up should be done to evaluate the development of complications. This report is about a 16-months-old boy who was admitted to the ER with frequent vomiting and swollen, reddened lips that appeared a few minutes after the accidental ingestion of air conditioner cleaner, which happened in the evening after iftar, 21 hours prior to admission. Clinical findings were first to third degree burns on lips and perioral skin, oropharyngeal mucosa, anterior of right axilla, shoulder, and right-back side of neck to upper back. Laboratory findings revealed anemia, leukocytosis, and thrombocytosis. Patient’s management includes NPO, total parenteral nutrition (first three days), broad-spectrum intravenous antibiotic, analgetic, PPI, corticosteroid, and sucralfate. Esophagoscopy and guided NGT insertion were done on the fourth day, and the diagnosis of esophagitis grade 2A was confirmed. Enteral feeding was started immediately and gradually increased until full oral feeding was achieved. The patient was hospitalized for ten days. It was concluded that in the case of caustic ingestion, the type of caustic substance and degree of injury determine the proper management of corrosive esophagitis, predict its complications, and follow-up planning.